PENGARUH SUBTITUSI PASIR NGANTANG DENGAN PASIR SILIKA TUBAN TERHADAP KUAT TEKAN BATA RINGAN DENGAN MENGGUNAKAN PROSES CELLULAR LIGHTWEIGHT CONCRETE (CLC) - Bobby Asukmajaya R. R.; Sugiharti (Jurnal Qua Teknika, 2022)
Indonesia as a developing country that is moving into a developed country, has a very large development point of the country. Development has begun to be leveled in many regions, of course, with rapid development, materials that support productivity, quality and efficiency are needed so that they can be utilized properly by the construction world. One that has been widely developed and used is the use of light bricks, with the light bricks the productivity of a construction work is much higher. The process of making light bricks is divided into 2, namely AAC and CLC, the process of making AAC light bricks is generally made by large companies because the manufacturing equipment is quite expensive, while for middle to lower industries generally use the CLC or Celullar Lightweight Concrete system, with a relatively simple process so that easy to apply. There have been many studies that have been developed to produce good CLC lightweight bricks, one of which is by making fine aggregate better, one of which is trying to substitute fine aggregate with Tuban silica sand with a substitution ratio of 0%, 25%, 50%, 75 %, and 100%, The results showed that the substitution with the most optimal mixture was at 75% substitution. This is because at 75% substitution, the compressive strength of lightweight CLC bricks has the greatest value but with a relatively low volume weight compared to other substitutions. In addition, the compressive strength with 75% substitution is in the highest quality III in SNI compared to the other mixtures.